Design for Longevity: A Framework to Support Product Developers in Identifying Products’ Optimal Lifetimes - Carlsson, Simon; Mallalieu, Adam (My University, 2021)
This project covers the development of the complete Design for Longevity framework which can be used to aid in the transition towards a circular economy and developing more sustainable products. The project consist of several phases, including a research phase, where a literature review is conducted. In this phase it is concluded of how product longevity should be managed in order to appropriately Design for Longevity, where it more specifically becomes clear that product developers should strive to design for a specific longevity, the optimal. The optimal product lifetime can in theory be obtained by considering the three contextual aspects; the user, the business and the resources efficiency. This way of thinking is used as the basis in the development phase, where a complete theoretical Design for Longevity framework is developed. The developed framework consist of a wholesome definition and mindset, along with a process and visualization tool to support the implementation of it. This framework is later evaluated in the evaluation phase, using semi-structured interviews within the Automotive industry, where several possible improvements are obtained. These improvements are resolved in the creation phase, resulting in an mediating implementation tool, the Design for Longevity Guide - A developed guide to ease the implementation of Design for Longevity. The Design for Longevity Guide is then validated in the validation phase, using a combination of a case study and a focus group within the Automotive industry. This entails the possibility to conclude that the Design for Longevity framework works both in theory and in practice. It can either be used and applied on less complex product to obtain feasible actions and smaller improvements, or serve as a facilitation tool to reflect and discuss upon possible improvements on more complex products. The results from the research-, development- and evaluation phase are presented to academia using a scientific article, Design for Longevity – A Framework to Support the Designing of a Product’s Optimal Lifetime.
Keywords: Product Longevity, Optimal Product Lifetime, Circular Economy,; Circular Design, Product Development, Design for X, Sustainability